Interpersonal Function in Course Webtoon Comic: A Systemic Functional Linguistics Analysis - Rudi Anshari; Dina Hanifa; Indri Octa Miransyah; Sennya x Sennya Nurditasari (Journal of English Language Teaching and Linguistics, 2021)
The purposes of this research are to analyze the webtoon with interpersonal functions in the term of mood and residue in Webtoon Comic that can be found by the writers, and the most dominant Mood type in a webtoon entitled "True Beauty" written by Lee Si-eun which the genre is drama. In this analysis applied Martin, Matthiessen & Painter Theory, 1997 that divided Mood Types are Declarative, Interrogative, and Imperative and Geoff Thompson Theory to analyze the Mood and Residue. In this research, the researcher used the documentation and analysis method. The writers used the documentation method to get the data and then do the analysis. Analysis of data that has been done from 49 Mood was found there are 33 Mood are Declarative, 10 Mood of Interrogative, and 6 Mood are Imperative. From the result of the data, it can be concluded that the most dominant Mood Type in the Webtoon Comic entitled "True Beauty" which was written by Lee Si-eun which the genre is drama is Declarative with 33 Mood in total 49 Mood.